Vital friends - Rath, Tom, 1975- (New York, NY : Simon & Schuster, 2007)
Presents findings from a massive study about the impact of friendships, plus eight vital roles your friends play in your life and at work
Title from container
Keywords: Employee motivation; Employee morale; Personnel management; Work -- Social aspects; Quality of work life; Friendship